Type 1 diabetes: a relatively unknown sibling of type 2 diabetes - Ahmad Mahfuz, Gazali (CodeBlue.org, 2021)
Given the global trend of increasing Type 1 diabetes incidences, more attention should be given to Type 1 diabetes in Malaysia. Every year on November 14, the world marks World Diabetes Day, which aims to create awareness about diabetes mellitus. In conjunction with World Diabetes Day, Health director-general Dr. Noor Hisham Abdullah has urged Malaysian to pay attention to this chronic disease